Strategi Bauran Pemasaran Produk Haji dan Umroh dalam Mencapai Target Penjualan di PT Ebad Group Jember - Nasir, Muhammad (Maddah: Journal of Advanced Da'wah Management Research, 2023)
Every company needs a good marketing mix strategy to introduce its products to the public. That way, the target that has been determined by the company in selling its products will be achieved. This research has a research focus and objectives, namely: (1) To describe the marketing mix strategy used at PT Ebad Group Jember in marketing Hajj and Umrah products (2) To describe the supporting and inhibiting factors of sales at PT Ebad Group Jember. Data were collected through observation, interviews and documentaries. Data is analyzed using data reduction, data presentation and conclusions. Data validity using method triangulation and source triangulation. The results of the research obtained are: Hajj and Umrah product marketing mix strategies in achieving sales targer at PT Ebad Group Jember using online and offline marketing mix strategies. On online media via Instagram, Facebook, Tiktok, WhatsApp. While offline through the distribution of brochures and visiting people's homes or door to door. Marketing mix guidelines in the form of 7P, namely : product, price, place, promotion, process, people and physical evidence. Supporting factors in achieving sales targets at PT Ebad Group Jember are: The spirit of the leadership and the PT Ebad Group Jember in their duties. And also the existence of an online marketing mix strategy. While the inhibiting factor in achieving sales targets at PT Ebad Group Jember is the obstacle in online promotion activities, limited knowledge about the media. In addition, there are many scams today, especially about Hajj and Umrah fraud.